Efficacy of platelet-rich plasma in meniscal repair surgery: a systematic review of randomized controlled trials - Giovanni Sergio Utrilla; Irene Roman Degano; Riccardo D’Ambrosi (Journal of Orthopaedics and Traumatology)
Abstract Purpose This study’s primary objective was to evaluate the effectiveness of platelet-rich plasma (PRP) administration for meniscal injuries treated with meniscal repair procedures (sutures), using radiologic measures and clinical scales. The secondary objective was to identify potential bias-inducing elements in the analyzed studies. Methods In December 2023, a systematic search was conducted in PubMed, Cochrane, Embase, and Scopus for randomized controlled trials. This review compares PRP with placebo. Three studies were finally selected. The risk of bias was assessed using Cochrane's Risk of Bias Tool 2. Radiologic evaluation of meniscal healing was measured with magnetic resonance imaging (MRI) and arthroscopic studies, while clinical evaluation was performed using four scales [Knee Injury and Osteoarthritis Outcome Score (KOOS), visual analog scale (VAS), International Knee Documentation Committee Subjective Knee Form (IKDC), and Western Ontario and McMaster Universities Index (WOMAC)] and by recording the incidence of complications. Results The three selected studies included 139 patients; of these, 76 (54.7%) were randomly assigned to the intervention group (PRP injection) and 63 (45.3%) to the control group (placebo). The mean age of the intervention group was 37.4 ± 7.5 years, while the mean age of the control group was 36.5 ± 9.2 years. There were 41 female patients (29.5%). The median follow-up duration was 27.58 ± 17.3 months. MRI evaluation did not show a significant improvement in the PRP group in any of the studies (p-value = 0.41–0.54). However, when assessed by the cumulative evaluation of MRI and arthroscopy, the cumulative failure rate was significantly better in the PRP group (p-value = 0.04–0.048). One study that evaluated isolated arthroscopy also showed significant improvement in the PRP group (p = 0.003). Regarding the VAS scale, no study demonstrated a significant difference, except for one study that showed significant improvement after 6 months and in the difference between the 3rd and 6th months. The KOOS scale yielded conflicting results; one study showed no significant difference, while the other two indicated significant improvement. The IKDC and WOMAC scales were evaluated in two studies, showing opposite results. All included studies reported no complications, and one study indicated no increased risk in the treatment group. Conclusions The results of this review indicate the necessity for further studies to make a definitive statement about the effectiveness of PRP administration in meniscal repair processes. Level of evidence Systematic review and meta-analysis of articles of level 1.